2021
DOI: 10.1007/s11102-021-01161-4
|View full text |Cite
|
Sign up to set email alerts
|

Managing pasireotide-associated hyperglycemia: a randomized, open-label, Phase IV study

Abstract: Purpose Pasireotide is an effective treatment for acromegaly and Cushing’s disease, although treatment-emergent hyperglycemia can occur. The objective of this study was to assess incretin-based therapy versus insulin for managing pasireotide-associated hyperglycemia uncontrolled by metformin/other permitted oral antidiabetic drugs. Methods Multicenter, randomized, open-label, Phase IV study comprising a core phase (≤ 16-week pre-randomization period follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 25 publications
(39 reference statements)
0
36
1
1
Order By: Relevance
“…Moreover, the study was the first one to unequivocally and directly demonstrate the efficacy of incretin drugs in treating PAS-induced carbohydrate metabolism disturbances. Interestingly, the study showed no differences in terms of impaired carbohydrate metabolism between the patients with acromegaly treated with PAS-LAR and those with Cushing's disease treated with PAS-LAR or subcutaneous PAS [28]. This finding is not consistent with those of other studies, where the rates and severity of hyperglycemia in patients with acromegaly treated with PAS-LAR seem to be lower than those in patients with Cushing's disease treated with subcutaneous PAS [55,58].…”
Section: Pasireotide In Acromegaly -Adverse Effectscontrasting
confidence: 76%
See 4 more Smart Citations
“…Moreover, the study was the first one to unequivocally and directly demonstrate the efficacy of incretin drugs in treating PAS-induced carbohydrate metabolism disturbances. Interestingly, the study showed no differences in terms of impaired carbohydrate metabolism between the patients with acromegaly treated with PAS-LAR and those with Cushing's disease treated with PAS-LAR or subcutaneous PAS [28]. This finding is not consistent with those of other studies, where the rates and severity of hyperglycemia in patients with acromegaly treated with PAS-LAR seem to be lower than those in patients with Cushing's disease treated with subcutaneous PAS [55,58].…”
Section: Pasireotide In Acromegaly -Adverse Effectscontrasting
confidence: 76%
“…PASinduced hyperglycemia was the most common adverse event observed in this study; however, it caused treatment discontinuation in only 5% of patients [27]. Demonstrating that incretin effect inhibition is one of the fundamental mechanisms behind PAS-induced hyperglycemia was the primary purpose for the use of GLP-1 receptor agonists and dipeptidyl peptidase 4 (DPP-4) inhibitors in PAS-induced hyperglycemia treatment [59] [28]. The study by Samson et al also showed that the patients randomized to receive incretin drugs had lower HbA1c levels and fewer hypoglycemic episodes in comparison with those reported in insulin-treated patients.…”
Section: The Management Of Pasireotide-induced Hyperglycemia In Cushi...mentioning
confidence: 85%
See 3 more Smart Citations